The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/02656736.2021.1923837
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time US-CT fusion imaging for guidance of thermal ablation in of renal tumors invisible or poorly visible with US: results in 97 cases

Abstract: Orsi (2021) Real-Time US-CT fusion imaging for guidance of thermal ablation in of renal tumors invisible or poorly visible with US: results in 97 cases,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Moreover, CT imaging has better tissue penetration, is more cost-effective, and can perform three-dimensional vascular reconstruction. Thus, US/CT dual-modal imaging is highly promising for improving real-time imaging contrast, acquiring clinical application anatomical information, and guiding and monitoring tumor ablation [ 122 124 ]. Yuan et al [ 125 ] developed a multifunctional nanodrug delivery system with multiple therapeutic and imaging functions.…”
Section: Cancer Theranosticsmentioning
confidence: 99%
“…Moreover, CT imaging has better tissue penetration, is more cost-effective, and can perform three-dimensional vascular reconstruction. Thus, US/CT dual-modal imaging is highly promising for improving real-time imaging contrast, acquiring clinical application anatomical information, and guiding and monitoring tumor ablation [ 122 124 ]. Yuan et al [ 125 ] developed a multifunctional nanodrug delivery system with multiple therapeutic and imaging functions.…”
Section: Cancer Theranosticsmentioning
confidence: 99%
“…Image-guided ablations, such as MWA, RFA, MWA plus RFA, CA and laser ablation have significantly progressed over the past years and they represent a useful toolbox for a multimodal approach to this disease [15,[20][21][22][23][24]. The most common shared indications…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, US-CT fusion imaging can be used for guidance during ablation of RCC [ 16 ]. For example, Mauri et al [ 17 18 ] reported that US-CT image fusion guidance allows for correct tumor targeting of renal tumors that are poorly visible, inconspicuous, or invisible with US alone. However, in that study, the RFA procedure did not use only US-CT fusion imaging guidance, and CT scans were simultaneously performed to confirm the position of the inserted electrode needle.…”
Section: Discussionmentioning
confidence: 99%